Two new species of Kalophrynus Tschudi, 1838 (Anura: Microhylidae) from the Annamite mountains in southern Vietnam - Vassilieva, Anna B.; Galoyan, Eduard A.; Gogoleva, Svetlana S.; Poyarkov, Nikolay Jr. A. (Zootaxa, 2014)
We describe two new mountain-dwelling microhylid species of the genus Kalophrynus from the southern part of the Annamite Mountains in Vietnam. The two new species differ from all known congeners in morphological characters and mtDNA; phylogenetically, they form a sister clade to the large-bodied K. interlineatus (1009 bp, 16S rRNA gene, mtDNA). Both species share the following characteristics: snout pointed in dorsal and lateral views, slightly sloping in profile; tympanum distinct, smaller than eye in diameter; toe webbing moderate; outer metatarsal tubercle present; light dorsolateral line absent. Kalophrynus cryptophonus sp. nov. from Loc Bao, Lam Dong Province is a small-sized species distinguishing from its congeners by a combination of: SVL 27.9–30.4 mm in males, 23.4 mm in female; canthus rostralis indistinct; males with large sharp conical spines on the skin covering mandible margins and finely asperous nuptial pads on the dorsal surface of fingers I–III; dark ocelli in the inguinal region usually present, small, without a light border; anterior palatal dermal ridge short, restricted to medial part of palate. Kalophrynus honbaensis sp. nov. from Hon Ba, Khanh Hoa Province is a medium-sized Kalophrynus, distinguishing from its congeners by a combination of: SVL 26.7–36.8 mm in males; canthus rostralis distinct; males without distinguishable spines on the mandible margins nor the nuptial pads; dark ocelli in the inguinal region present, large, without a distinct light border, anterior palatal dermal ridge developed, parallel to posterior one. Kalophrynus cryptophonus sp. nov. reproduces in hollow bamboo stems; we describe larval morphology and bioacoustics of this species in relation to phytotelm breeding. A review of the distribution of the genus Kalophrynus in Indochina is provided.